Settlement of administrative contract disputes in international commercial arbitration - Al-Ali, Khalfan Mater Khalfan Aljabry (2023)
This study focused on the issue of settling administrative contract disputes in international commercial arbitration. In May 2018, the government of United Arab Emirates (UAE) approved the Federal Law No. (6) of 2018 on Arbitration. Recent economic developments led to an increase in international contracts and interest in international arbitration, due to the ease and flexibility that international arbitration provides in international transactions. Generally, the aim of resorting to arbitration was to seek for protection and gain profits while ensuring integrity, transparency and impartiality in the Court of Arbitration, and what may arise from the changes required by the economic policy of the state, especially the legislation related to economic development. The study discussed the subject of international arbitration in the UAE, with a focus on how the international arbitration award in international administrative contracts was issued and appealed according to the Arbitration Law 6-2018. The researcher used the comparative analytical method to achieve the objectives of the study, by analysing the Emirati legal texts and relevant international laws. The study concluded that UAE legislators considered the possibility of resorting to arbitration as an alternative method of resolving administrative contract disputes based on the provisions of the Arbitration Law 6-2018. Finally, the study recommended that some legal texts regarding the selection of the law applicable to the international dispute be added to the internal arbitration law.